(3bhi GdCZPjI dLGdjfhSs - (3Mfjf Hf ESMGb , CHh RjO Mfjf Hf ESMGb GdYHGOj,J (B260 (3g` s
(3ChdgG (B:s
(3bGd LGdjfhS (B: (3bO hVY GdcJH ai bhi GdCZPjI cKjQkG ef Phi GdaVd ef GdCWHGA s
(3BNQgG (B:s
(3hcPdc jNJda GdCeQ HMSH GNJdGa GdUfGYGJ hGdYGOGJ hGdHdOGf GdJi jWhd JUQage hJbdHge ajgG OgQkG WhjdkG s
(3KdGK ebGdGJ cd ebGdI CHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B287 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B87s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B20 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B147 s
Keywords: (3GdWHs